1986
DOI: 10.1002/jsfa.2740370604
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the presence and significance of theanine in the tea plant

Abstract: Theanine was determined in black teas and tea plants by a combination method of thin-layer chromatography (t.1.c.) and densitometry. It was shown that in 20 samples of black tea from different qualities and sources the amount varied from 0.33 to 1.59 g 100 8-l dry wt. The highest quality black teas possessed the lowest amount of theanine, but it is subject to chemical degradation during black tea manufacture. The investigation of physiological function of theanine in the tea plant showed that during germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
4
30
0
Order By: Relevance
“…Total N concentrations in young shoots, roots and stem decreased from the beginning to the end of sampling (Fig. 1c), which is in line with earlier findings that the total N content of young shoots decreased gradually with flush growth, and those in leaves, stem and roots tended to decrease when the tea plants became older (Feldheim et al 1986). On the other hand, it was also likely that the decreasing N concentrations in stem and roots were caused by N remobilization from these organs to support the rapid growth of the young shoots.…”
Section: Urea-n Absorption By Leaves Of Tea Plants In the Solution Exsupporting
confidence: 91%
“…Total N concentrations in young shoots, roots and stem decreased from the beginning to the end of sampling (Fig. 1c), which is in line with earlier findings that the total N content of young shoots decreased gradually with flush growth, and those in leaves, stem and roots tended to decrease when the tea plants became older (Feldheim et al 1986). On the other hand, it was also likely that the decreasing N concentrations in stem and roots were caused by N remobilization from these organs to support the rapid growth of the young shoots.…”
Section: Urea-n Absorption By Leaves Of Tea Plants In the Solution Exsupporting
confidence: 91%
“…The tea had stems as well as leaf material in it. As reported in a previous study 25, it is well known that theanine is often found at a higher concentration in stems than in leaves. The stems are harder to grind into small pieces than the leaves and therefore the particle sizes of the ground stem material may have been bigger than the particle sizes from the ground leaf material.…”
Section: Resultssupporting
confidence: 71%
“…These results suggest that theanine can be synthesised from glutamic acid and ethylamine derived from alanine in all parts of tea seedlings. However, 15 supplied exogenously to intact seedlings was converted to theanine mainly in roots [24]. Amino acids stored in cotyledons may also be utilised for theanine synthesis in all parts of seedlings.…”
Section: Location Of Theanine Biosynthesismentioning
confidence: 99%